Limited Resection of the Duodenum for Nonampullary Duodenal Tumors, with Review of the Literature. Issue 11 (November 2016) - Hashimoto, Daisuke; Arima, Kota; Chikamoto, Akira; Taki, Katsunobu; Inoue, Risa; Kaida, Takayoshi; Higashi, Takaaki; Imai, Katsunori; Beppu, Toru; Baba, Hideo
The surgical management of duodenal pathology is challenging because of its retroperitoneal position and shared blood supply with the pancreas. We present three types of limited resection of the duodenum for the removal of superficial or small nonampullary duodenal (NADL) lesions, and also a review of the English literature regarding management, such as endoscopic resection and limited duodenal resection. Ten cases underwent limited resections of the duodenum for superficial or small NADL lesions from 2011 to 2015. Pancreas-preserving segmental duodenectomy was performed in three cases, local full-thickness resection was performed in three and transduodenal submucosal dissection was performed in four. One patient experienced pancreatic fistula as a postoperative complication. Postoperative pathological diagnosis were adenoma (n = 2), mucosal adenocarcinomas (n = 5), and neuroendocrine tumor (n = 3). Surgical margin was negative in all cases, and no patient has experienced postoperative recurrence or metastasis. Limited resections of the duodenum were feasible and safe procedures for patients with superficial or small NADL lesions. Laparoscopic surgery may be considered in treatment for these tumors. However, the optimal surgical management for superficial or small nonampullary duodenal lesions remains controversial.